The effects of acetate ions (CH3COO-) on electrochemical behavior of copper in chloride solutions - Kilincceker, Gueray; Galip, Hasan (Elsevier Science Sa, 2008)
The corrosion behavior of copper has been investigated in presence of acetate ions, at various temperatures in highly corrosive chloride solution. For this aim, potentiodynamic and EIS (electrochemical impedance spectroscopy) measurements were used. Corrosion rates have been determined by extrapolating the polarization curves. The role of temperature, ionic species and the effect of oxide film formation have been interpreted in aspect of anodic and cathodic processes rate. Thermodynamical properties Delta G (free enthalpy), Delta H (enthalpy), Delta S (entropy) and E-a (activation energy) values have been evaluated with help of current-potential measurement results. The experimental results showed that acetate ions have decreased the corrosion rate of copper in chloride containing solutions of pH 8.5. It was also shown that the acetate ions could provide protection behavior at elevated temperatures. The changes in thermodynamic properties showed that acetate ions formed stable and protective complex which physically adsorbed on the surface. The Delta G value decreased and E-a values increased in presence of acetate ions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: copper; electrochemical techniques; corrosion; thermodynamic properties